Perbedaan Pengaruh Model Latihan Konsentrasi Dan Tanpa Model Latihan Konsentrasi Terhadap Peningkatan Kemampuan Shooting Game Atlet Petanque Undikma - Lubis, Muhammad Ridwan; Permadi, Andi Gilang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This research is motivated by the inconsistency in the shooting ability of athletes in shooting games in Petanque sports, both at the regional and national levels. This study aims to determine the effect of the concentration training model on the improvement of the shooting game ability of Undikma Petanque athletes. This study used an experimental method with the design of